Self-harm in immigration detention: political, not (just) medical - Aitchison, Guy (Journal of medical ethics, 2024)
Self-harm within immigration detention centres has been a widely documented phenomenon, occurring at far higher rates than the wider community. Evidence suggests that factors such as the conditions of detention and uncertainty about refugee status are among the most prominent precipitators of self-harm. While important in explaining self-harm, this is not the entire story. In this paper, we argue for a more overtly political interpretation of detainee self-harm as resistance and assess the ethical implications of this view, drawing on interviews with detainees from Australia’s offshore system. Self-harm by detainees is not only a medical ‘condition’ arising in response to oppression but a form of political action to lessen or contest it. We first establish how self-harm could be conceptualised as resistance. We then discuss its political purpose, noting it serves at least three functions: intrinsic, instrumental and disruptive or coercive. Viewing detainee self-harm as political resistance is a supplement to (rather than a substitute for) a medical approach. However, conceptualising self-harm this way has several advantages, namely, moving away from the idea that such behaviour is ‘maladaptive’, recognising detainees as political agents, combatting government claims of ‘manipulation’ and ‘blackmail’ and clarifying the duties of healthcare workers who work in detention.